The specificity and generality of the characters of Ismail Kadare’s novels - Farizi, Arlind (Technium Social Sciences Journal, 2026)
The study will be based on the main hypothesis that Ismail Kadare’s characters, through their typology, bring this writer closer to his immediate followers of the period of modernism and postmodernism . Throughout the narrative, the characters appear to us with their actions, thoughts, monologues, the thoughts of other characters and through the portrayals of the narrator. Although the separation between character and action has been made since antiquity by Aristotle and by various theorists later, giving priority to one or the other, when talking about the realistic novel, perhaps the most stable is the idea that character and action are inseparable, because in every breath they merge into each other. They are in a symbiotic relationship and, through one, the reader manages to get to know the other, by analyzing the action, reaches its causes and from horizontal analysis, moves to vertical. If we rely on the fact that, through narratives, we can recognize ourselves as active personalities who exist in time , then, through the narration of events in " The General of the Dead Army", "Concert at the End of Winter", "Chronicle in Stone" and "Lul Mazreku" , we can recognize types of characters and each of them carries characteristics that differentiate him from others, make him special, but also characteristics that align him, not only with other characters who have the same position in society, the same goals in life, but also with real people, which allows the reader to have a clearer perception of the world and the people who live in it, and in addition, of himself. Thus, in Kadare’s four novels, each character represents at the same time the class to which he himself belongs, therefore, he is the bearer of collective and individual characteristics. In addition, we do not know them only in one sphere of life, but in the moments that build its entirety, therefore, in most cases, we are not dealing with one-dimensional characters, but multidimensional. They appear to us in the family circle, but also in society, they are in conflict with themselves, with the close circle where they live (the family), with people of the same class, but also with those of the opposing class, then with nature and in many cases even with God.